71.4k views
3 votes
(-18x^2+12x-2)*(x^3+12x^2+48x+64)

User Hihikomori
by
5.7k points

1 Answer

5 votes

Answer:

-18x^5-204x^4-722x^3-600x^2+672x-128

Step-by-step explanation:


( - 18 {x}^(2) + 12x - 2)


( {x}^(3) + 12 {x}^(2) + 48x + 64)

There are multiple ways to solve this for example the foil method or the box method. I prefer to do the box method.

First we are going to set it up

After we set it up we have to solve it so first we are going to multiply


{x}^(3) * - 18 {x}^(2) = - 18 {x}^(5)

We have to add the exponent


- 18 {x}^(2) * 12 {x}^(2) = - 216 {x}^(4)


- 18 {x}^(2) * 48x = - 864 {x}^(3 ) \\ - 18{x}^(2) * 64 = - 1152 {x}^(2) \\ 12x * {x}^(3) = 12 {x}^(4) \\ 12x * 12 {x}^(2) = 144 {x}^(3)


12x * 48x = 576 {x}^(2) \\ 12x * 64 = 768x


- 2 * {x}^(3) = - 2 {x}^(3) \\ - 2 * 12 {x}^(2) = - 24 {x}^(2) \\ - 2 * 48x = - 96x \\ - 2 * 64 = - 128

Now we have to add them

-18x^5 stays because there is nothing to add to

Now we add the rest


-216 {x}^(4) + 12 {x}^(4) = - 204 {x}^(4)


- 864 {x}^(3) + 144 {x}^(3) + - 2 {x}^(3) = - 722 {x}^(3)


768x - 96x = 672x

And -128 stays the same


- 1152 {x}^(2) + 576 {x}^(2) - 24 {x}^(2) = - 600 {x}^(2)

The answer is

-18x^5-204x^4-722x^3-600x^2+672x-128

(-18x^2+12x-2)*(x^3+12x^2+48x+64)-example-1
User Agbodike
by
4.8k points